Beyond compliance: A strategic foresight framework for workforce nationalization in a multinational offshore drilling subsidiary - Alvino Resa Julian Kesaulya; Achmad Fajar Hendarman (Priviet Social Sciences Journal, 2026)
Resource-nationalist labor regulations are reshaping Indonesia's upstream oil and gas sector by requiring multinational offshore drilling subsidiaries to localize senior command roles without compromising safety, client confidence, or operational continuity. This study developed a strategic framework for PT. Ombak Biru Offshore (OBO) to transform workforce nationalization under SKK Migas PTK-007 Revision 5 from a compliance obligation into a source of sustainable competitive advantage. Using a qualitative explanatory single-case design, this study triangulates semi-structured key informant interviews with regulatory documents, internal company records, anonymized parent-company records, and industry benchmark reports. The analysis applies Hines and Bishop's (2015) Strategic Foresight framework, integrated with the Resource-Based View, Dynamic Capabilities, and SECI knowledge creation theory. The findings show that Rig Manager readiness requires technical-operational mastery, commercial and client management capability, leadership, and tacit knowledge transfer competence. Local talent progression is driven by the Great Crew Change, regulatory enforcement, the national 1 million Barrels of Oil Per Day (BOPD) target, and client ESG expectations but is constrained by long tacit knowledge transfer cycles, dependency on parent company trainee structures, certification cost paradoxes, and talent flight economics. This study proposes a dual-pathway localization framework supported by three enablers: Organizational Architecture, Human Capital Development, and Knowledge Transfer and Retention. It recommends establishing a Local Talent Development Committee, implementing an integrated Talent Management Information System, strengthening PTK-007 and PTK-018 engagement, introducing certification support, reforming Tingkat Komponen Dalam Negeri (TKDN) calculation to reward capability building, and developing outcome-based regulatory coordination. The framework offers a practical roadmap for building Indonesian offshore command capability by 2037 while preserving safety and continuity and creating a sustainable competitive advantage.